2012
DOI: 10.3389/fphar.2012.00135
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Immunomodulatory Effects of Polysaccharides from Broken-Spore of Ganoderma lucidum

Abstract: The antitumor and immunomodulatory activity of broken-spore of Ganoderma lucidum polysaccharides (Gl-BSP) were investigated in vivo and in vitro. It was showed that Gl-BSP (50, 100, and 200 mg kg−1) exhibited antitumor effect against Sarcoma 180 (S180) in BALB/c mice. The Gl-BSP was not cytotoxicity in S180 cells and PG cells (human lung carcinoma cell) in vitro. However, serum from Gl-BSP-treated S180-bearing mice significantly inhibited S180 and PG cells proliferation in vitro. Moreover, Gl-BSP promoted the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 37 publications
(34 reference statements)
1
45
0
2
Order By: Relevance
“…IFN-γ, which is secreted by stimulated Th1 cells, has a crucial role in modulation of various immune processes. The activated Th1 cells are not only involved in production of cytokines, but also stimulate the production of different types of IgG, which are released by B lymphocytes in the immune system [28]. These results support the possible value of the metabolites for reversing pathophysiological conditions related to immunological background of diseases, particularly in immunodeficient and cancer patients or general immunosupression subsequent to chemotherapy ( active components of the metabolites and cell surface molecules or other compartments of the immune system.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…IFN-γ, which is secreted by stimulated Th1 cells, has a crucial role in modulation of various immune processes. The activated Th1 cells are not only involved in production of cytokines, but also stimulate the production of different types of IgG, which are released by B lymphocytes in the immune system [28]. These results support the possible value of the metabolites for reversing pathophysiological conditions related to immunological background of diseases, particularly in immunodeficient and cancer patients or general immunosupression subsequent to chemotherapy ( active components of the metabolites and cell surface molecules or other compartments of the immune system.…”
Section: Discussionmentioning
confidence: 67%
“…A number of studies have identified immunomodulatory compartments of microbial products such as bacterial toxins, bacterial polysaccharides and secondary metabolites that have poteintal in treating certain pathological situations [2,4,6,[17][18][19][20][21][22][23][24][25][26][27][28]. Several substances, including components of bacterial cell walls, have been reported to modulate innate immune responses [1,7,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…sinica.edu.tw, or chwong@gate.sinica.edu.tw. growth in vitro, but the pure Reishi extract alone did not induce similar effects (24,25). Thus, we conducted a synthetic glycan microarray analysis to investigate whether F3-induced antisera could recognize biologically important glycan epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…We first conducted a study in an animal tumor model using C57BL/6J mice with implantation of murine Lewis lung carcinoma (LLC1) cells to investigate the antitumor activity of F3. Briefly, LLC1 cells were transplanted s.c. into mice, and then F3 (24,52,120, and 240 mg/kg body weight per mouse dissolved in PBS) was administered i.p. once every other day, and the process was repeated for 28 d. As shown in the tumor growth curves (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of cancer patients (including those with sarcoma) succumb to recurrence, metastasis, or therapy-related life-threatening complications (18,19), in which chemotherapy-induced immunosuppression plays a major role. Certain polysaccharides extracted from various Chinese herbs have been demonstrated to possess antitumor properties in recent studies, including the polysaccharides from Ganoderma lucidum (20), Ganoderma atrum (21) and ginseng neutral (22). One of the most obvious advantages of herbal-extracted polysaccharides is their low incidence of side effects and potent anticancer activity.…”
Section: Discussionmentioning
confidence: 99%